2017
DOI: 10.1371/journal.pone.0171136
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of first trimester attendance at antenatal care clinics in the Amazon region of Peru: A case-control study

Abstract: ObjectiveTo identify determinants which influence the timing of the first antenatal care (ANC) visit in pregnant women.DesignRetrospective matched nested case-control study.SettingTwo health centres, Belén and 6 de Octubre, in the Peruvian Amazon.PopulationAll pregnant women who had attended ANC during the years 2010, 2011, and 2012.MethodsAll cases (819 women initiating ANC in their first trimester) were selected from ANC registries from 2010 to 2012. A random sample of controls (819 women initiating ANC in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 16 publications
5
23
0
4
Order By: Relevance
“…Strategies to increase ANC contacts must target these women. Our findings were consistent with other studies [1,[24][25][26][27][28]: one of them examined coverage and timing of ANC among the poor in Mesoamerican countries and showed that education, parity and marital status were factors predicting timely ANC initiation [24]. Similarly, Gupta et al looked at utilization of antenatal care in Tanzania between 1990 and 2010 and found that urban residence, lower birth order and ANC initiation before four months of gestation were associated with utilization of at least four antenatal care visits [1].…”
Section: Discussionsupporting
confidence: 90%
“…Strategies to increase ANC contacts must target these women. Our findings were consistent with other studies [1,[24][25][26][27][28]: one of them examined coverage and timing of ANC among the poor in Mesoamerican countries and showed that education, parity and marital status were factors predicting timely ANC initiation [24]. Similarly, Gupta et al looked at utilization of antenatal care in Tanzania between 1990 and 2010 and found that urban residence, lower birth order and ANC initiation before four months of gestation were associated with utilization of at least four antenatal care visits [1].…”
Section: Discussionsupporting
confidence: 90%
“…Enabling pregnant women to continuously receive ANC, skilled birth attendance at delivery, and postnatal care (PNC) are reported to have a significant positive impact on overall MNCH indicators [ 7 ]. In particular, receiving ANC has been shown to be one of, if not the best, indicator of positive pregnancy outcomes, significantly contributing to the reduction of maternal morbidity and mortality [ 5 , 8 ]. ANC are used to identify pregnancy risks and provide care for pregnant women who might be susceptible to a wide variety of potentially fatal conditions such as HIV, malaria, tuberculosis, anemia, and malnutrition [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of women initiating their ANC in their first trimester, although higher than previous reports from Iquitos (32.5%) and other developing countries, is lower than the national figure (79.8%) [6,16,[32][33][34][35][36][37][38]. This could be due to the Amazonian culture in Iquitos, resulting in some women visiting practitioners of traditional Amazonian medicine before accessing ANC later in pregnancy [16,39].…”
Section: Discussionmentioning
confidence: 76%
“…As well as women missing appointments, the lower proportion of women attending according to the MoHP schedule could be due to delayed initiation of ANC, resulting in an absence of appointments in earlier gestational windows. Community health promotion and education activities could be implemented within Iquitos to encourage more women to access ANC in their first trimester to meet WHO recommendations and encourage subsequent appointments to be attended according to the MoHP schedule [16,40]. Trials of conditional cash transfer systems as an incentive for attending ANC have also been successful in improving rates of women attending antenatal appointments in Peru [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation